STRATEGI PENGEMBANGAN AGROINDUSTRI DAPOER RENDANG RIRY PAYAKUMBUH - Lestari, Suzie; Syahza, Almasdi; ', Suarman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract : The purpose of this study aims to analyze the development strategy of agroindustry Dapoer Rendang Riri Payakumbuh. The subjct of this study is Agroindustry Dapoer Rendang Riry in Payakumbuh. The instruments of data collection were an open quetionnare, interviews and documentation. Data ware analyzed by using SWOT matrix. The result showed that the alternative strategies that can be applied by the company such as maintaining the quality of products and services, increasing the market share, expanding the utilization of technology in the company's activities, developing professional management system, cooperating with raw material suppliers, increasing promotion with exhibition and sponsorship, improve the product packaging system, and expand the parking lot. The result analysis shows that company has the strength that can be utilized in reaching the existing opportunity, wiht the main of strategies such as maintaining the quality of products and services, and increase market share.Keywords: strategi of development, agroindustry